1990
DOI: 10.1002/j.1552-4604.1990.tb03491.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Comparison of Metoprolol CR/ZOK Once Daily with Conventional Tablets Once Daily and in Divided Doses

Abstract: Four studies of identical design, each on 18 young healthy subjects, were undertaken to study the pharmacokinetics and beta 1-receptor blockade at steady state after a once daily dose (od) of 100, 200, 300 and 400 mg of metoprolol CR/ZOK (a new controlled release preparation) in comparison with 100 mg dosages (od, bid, tid and qid, respectively) of conventional metoprolol tablets (CT). All studies were of randomized three-way crossover design with 7-day double-blind treatment periods separated by 7-day single-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 15 publications
2
43
0
Order By: Relevance
“…The results from this study, which for the first time compared once daily metoprolol CR/XL 200 mg with multiple dosing of metoprolol IR 50 and 100 mg in patients with acute myocardial infarction, are in agreement with pharmacokinetic results from studies in healthy subjects [16] and in heart failure patients [17]. …”
Section: Discussionsupporting
confidence: 72%
“…The results from this study, which for the first time compared once daily metoprolol CR/XL 200 mg with multiple dosing of metoprolol IR 50 and 100 mg in patients with acute myocardial infarction, are in agreement with pharmacokinetic results from studies in healthy subjects [16] and in heart failure patients [17]. …”
Section: Discussionsupporting
confidence: 72%
“…According to one report, atenolol, bisoprolol, and metoprolol were more effective than other β-blockers in managing resting HR in CHD patients 9. Previous studies of multiple patient groups have demonstrated that changes in both 24-h average HR and resting HR were related to the dosage of β-blocker administered 18, 19. In a study involving Chinese CHD patients who were β-blocker-naive, 42.5% and 79.4% of the patients achieved a HR of less than 70 bpm after one and two months of metoprolol succinate treatment, respectively 18.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that metoprolol CR/ZOK produces a more even 1-blockage over 24 h. This is determined by expressing the percentage reduction in exercise heart rate in relation to placebo at intervals throughout the 24 h and comparing the results with those of atenolol and conventional metoprolol tablets (17,20,(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%